Fungsi Pengawasan PT ASDP terhadap Penyedia Jasa Penyeberangan di Pelabuhan Kolaka - Ningsih, Sudarmi; Agusman, Yudi; Asis, Laode Asrun; Hidayat, Rahmat; Muzakkir, Abd. Kahar (CV. Social Politic Genius (SIGn), 2022)
This research aims to analyze the supervisory function of PT ASDP regarding the services of ferry companies at Kolaka Port. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show the discrepancies between theoretical and practical aspects of PT ASDP supervision, particularly in direct versus indirect supervision within social and economic interactions on ships, notably concerning ongoing mat rental practices despite existing reprimands and routine inspections. Additionally, the lack of regulation for mat rental practices creates legal uncertainties and potential disturbances, suggesting a more comprehensive supervisory approach encompassing preventive, repressive, and internal and external elements to address these issues. The presence of mats in outdoor areas causes passenger discomfort, and interactions between the government and related parties in resolving these issues underscore the necessity for evaluating and refining existing supervision mechanisms. Therefore, it is recommended that PT ASDP enhances the effectiveness of both direct and indirect supervision of ferry services at Kolaka Port by integrating a more comprehensive supervisory approach, including preventive aspects to anticipate potential issues and repressive measures for violations. It necessitates reviewing and refining ship regulations to incorporate clear rules regarding mat rental practices and ensure strict supervision of these regulations' enforcement. Related government agencies are advised to collaborate closely with PT ASDP to develop effective policies and supervisory mechanisms and conduct public awareness campaigns to underscore the importance of regulatory compliance. NGOs could play a role in monitoring the implementation of supervision and providing constructive feedback for improvements. The community is also encouraged to monitor and report discrepancies to support collective efforts to enhance future ferry service quality.